Characterization of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli in Diarrhoeal Faeces from 0 to 5-Year-Old Children Attending Public Hospitals in Franceville, Gabon - Anicet-Clotaire Dikoumba; Pierre Philippe Mbehang Nguema; Leresche Even Doneilly Oyaba Yinda; Romeo Wenceslas Lendamba; Jean Constan Obague Mbeang; Guy Roger Ndong Atome; Christophe Roland Zinga Koumba; Sylvain Godreuil; Richard Onanga (Antibiotics)
Background: In Gabon, studies on the characterization of extended-spectrum beta-lactamase-producing Escherichia coli in young children with diarrhoea are almost nonexistent. The objective was to evaluate the prevalence of antibiotic resistance to extended-spectrum beta-lactamase-producing Escherichia coli in children at public hospitals in Franceville, Gabon. Methods: Seventy diarrhoea faecal samples were collected from children aged 0–5 years. The culture and isolation of colonies were carried out on MacConkey agar. The colonies were identified using VITEK 2. The determination of the extended-spectrum beta-lactamase’s profiles was accomplished using the double disk method. The identification of phylogroups and pathotypes was performed by PCR. Identification of the ESBL genes was performed by sequencing. Results: A total of 26 strains of Escherichia coli (33.0%) were identified from 78 bacterial isolates. Twenty (77.0%) Escherichia coli strains carried extended-spectrum beta-lactamases blaCTX-M-15 and 5.0% carried blaSHV-12 subtypes. Phylogroup D (62.0%) was predominant, followed by B1 (12.0%), B2 (8.0%) and E (4.0%). The bacterial pathogens causing diarrhoea were enterohemorrhagic E. coli (12.0%), typical enteropathogenic Escherichia coli (8.0%), atypical enteropathogenic Escherichia coli (4.0%), Enteroaggregative Escherichia coli (4.0%) and enteroinvasive E. coli (4.0%). Conclusions: This study showed a high prevalence of extended-spectrum beta-lactamase, Escherichia coli of phylogroup D and pathotype enterohemorrhagic Escherichia coli in children under 5 years old in public hospitals in Franceville, most probably due to the misuse or inappropriate consumption of beta-lactams.